Human relations strategies for success - Lamberton, Lowell H.; Minor, Leslie; Zeigler, Demitrius (McGraw Hill LLC, 2022)
"Throughout our years of teaching, administration, running small businesses, and consulting in the fields of social science and organizational behavior, we have become increasingly aware of the need for a textbook that is down to earth, experience based, and grounded in sound research and theory. We believe strongly in the importance of understanding the relationship between self-awareness and human relations, and, by extension, the relationship between human relations skills and ongoing career success. We encourage building self-awareness, growth, and success skills inside the context of the real world. What realistic strategies and techniques can we teach our stu-dents to encourage their growth in human relations success, on and off the job site? How can students tap into the power that comes from working well in one-on-one situations, in groups, and in organizations large and small?"--